NCOG-27. INCREASED OVERALL SURVIVAL AMONG RACIAL MINORITIES AND SUBOPTIMAL USE OF STANDARD OF CARE TREATMENT IN GLIOBLASTOMA MULTIFORME. (9th November 2020) - Boisclair, Stephanie; Samuels, Shenae; Khunger, Arjun; Wietecha, Delia A; Cohen, Alejandro Lopez; King, Kelly; Sareli, Candice; Jacques, Jessica; Salzberg, Mathew; Vulfovich, Michel; Hunis, Brian; Raez, Luis E; et al.
Abstract: Glioblastoma Multiforme (GBM) is the most common primary central nervous system (CNS) tumor and is always considered grade IV given its aggressive nature and poor overall survival (OS). Despite advancements in surgical techniques and cancer therapies, GBM treatment has remained the same since 2005: total resection followed by temozolomide and radiation. We hypothesized that OS has increased over the years and is similar among all races/ethnic groups without reduction of mortality based upon treatment facility. METHODS: The National Cancer Database from 2004-2016 was utilized to obtain demographic, tumor and treatment factors of GBM (excluding gliosarcomas). Multivariate Weibull regression model was used to evaluate prognostic factors for OS in months(m). RESULTS: A total of 119, 496 patients were identified. There was a significant difference(P=0.000) in OS for patients diagnosed in 2012-2016 (10.2m) compared to 2008-2011 (9.2m) and 2004-2007 (8.1m). Among racial groups, the highest incidence was among whites (91.8%) whom also had the lowest OS (9.0m), followed by Blacks (10.5m), Hispanics (11.7m) and Asians (12.9m)(P=0.000). Patients with unilateral tumors (72.1%) and tumor size < 3cm (18.3%) had an increased OS (9.8m-10.2m and 11.2m, respectively) compared with patients having bilateral tumors or larger size ≥ 3cm (OS of 4.8m and 8.9m, respectively)(P=0.000). Increasing age (HR=1.03) and comorbidity score ≥ 3 (HR=1.40) were independent predictors of death (P=0.000), while female sex (HR=0.88), Asian ethnicity (HR=0.75) and treatment at an academic/research facility (HR=0.86) were independent predictors of survival(P< 0.01). Only 60.1% of patients (n=59, 112) received ideal treatment (surgery, chemotherapy and radiation), while only 3.2% of all GBM patients received palliative care. DISCUSSION: Decreased OS was found among white race, large and bilateral tumors. Despite a statistically significant, although minimal, increase in OS since 2004-2007, there is notable underutilization of ideal treatment and palliative care. Further studies should focus on access inequalities and limitations to treatment.